Antibacterial properties of silver nanoparticles and their membranotrophic action - Gabrielyan, Lilit S.; Trchounian, Armen A. (Experimental Biology and Biotechnology, 2021)
Nowadays, metal nanoparticles (NPs) can be considered as alternative agents for overcoming antibiotic resistance. The effect of silver NPs on gram-positive (Enterococcus hirae ATCC9790, Staphylococcus aureus MDC5233) and gram-negative (Escherichia coli K-12, Salmonella typhimurium MDC1759) bacteria have been investigated in this work. Silver NPs demonstrated antibacterial activity against the bacteria used, expressed in the decrease of the specific growth rate and the number of colony forming units. Moreover, the bactericidal effect of silver NPs on gram-positive bacteria was more pronounced than on gram-negative bacteria. In order to find out the mechanisms of NPs’ effects, the change of the redox potential, the hydrogen (H2) production ability, and the protons flux across the bacterial membrane have been also studied. The addition of NPs led to inhibition of H2 yield and to change of the energy-dependent proton flux through Fo F1-ATPase, indicating the silver NPs effect on the activity of membrane-bound enzymes. The data obtained point out that silver NPs show a pronounced antibacterial effect against the studied bacteria and can be used in biomedicine.